Implementation of fiber-optical sensors into coreless filament-wound composite structures. (15th June 2022) - Mindermann, Pascal; Gil Pérez, Marta; Kamimura, Naoki; Knippers, Jan; Gresser, Götz T.
Highlights: Integration of fiber-optical sensors into the coreless filament winding process. Data visualization and analysis methods for strain field sensor data. Comparative analysis of the strain field and structural numerical simulation. Abstract: Fiber-reinforced composite structures manufactured by coreless filament winding (CFW) are adaptable to the individual load case and offer high, mass-specific mechanical performance. However, relatively high safety factors must be applied due to the large deviations in the structural parameters. An improved understanding of the structural behavior is needed to reduce those factors, which can be obtained by utilizing an integrated fiber-optical sensor. The described methods take advantage of the high spatial resolution of a sensor system operating by the Rayleigh backscatter principle. The entire strain fields of several generic CFW samples were measured in various load scenarios, visualized in their spatial contexts, and analyzed by FEM-assisted methods. The structural response was statistically described and compared with the ideal load distribution to iteratively derive the actual load introduction and prove the importance of the sensor integration. The paper describes methods for the sensor implementation, interpretation and the calibration of structural data.